2020
DOI: 10.21203/rs.3.rs-51355/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Justice in Health System; a Neglected Component of Academic Nursing Education: A Qualitative Study

Abstract: Background : In recent decades, increasing social and health inequalities all over the world has highlighted the importance of social justice as a core nursing value. Therefore, proper education of nursing students is necessary for preparing them to comply with social justice in health systems. This study is aimed to identify the effective factors in teaching the concept of social justice in the nursing curriculum. Method : This is a qualitative study, in which the conventional content analysis approach was em… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…In their study, Khan et al also discussed how e-learning has emerged as a new method to bolster the learning process and that higher-quality electronic content leads to more e cient e-learning. In a study by Habibzadeh et al (2019), both the traditional method of education and e-learning increased learners' knowledge on cardiac dysrhythmia, but e-learning was more effective (31). On the contrary, some studies have shown that the traditional method of education is more effective than e-learning, including a study by Kazemnezhad et al (2016) (32), which is inconsistent with the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…In their study, Khan et al also discussed how e-learning has emerged as a new method to bolster the learning process and that higher-quality electronic content leads to more e cient e-learning. In a study by Habibzadeh et al (2019), both the traditional method of education and e-learning increased learners' knowledge on cardiac dysrhythmia, but e-learning was more effective (31). On the contrary, some studies have shown that the traditional method of education is more effective than e-learning, including a study by Kazemnezhad et al (2016) (32), which is inconsistent with the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…These same authors noted that educators report high workload and a lack of resources, which contributed to their discomfort in teaching students about social justice. The issue is further compounded because educators often use ineffective teaching strategies (Habibzadeh et al, 2021). This aligns with Prendegast and colleagues' (2020) position that, "while nursing schools are educating students to work with racialized patients and staff, schools are providing little to no knowledge or understanding about systemic racism" (par 3).…”
Section: Micro-level Challengesmentioning
confidence: 89%